Religious-social leadership values and principals" morality in Christian school - Arjanto, Paul (HTS teologiese studies, 2024)
Leaders’ morality in the context of principals in Christian school is of great significance in the education environment. However, there are gaps between religious insights, western education and principal’s leadership in Christian schools in Indonesia. Anthropological, social, cultural and other differences can pose hindrances to the effective implementation of external ideas. Therefore, this research emphasises the importance of embracing moral religious leadership values from local cultural heritage that are appropriate to the Indonesian context. Tonaas and Walian leadership in Minahasa are promising alternatives that can contribute to the discourse on principals’ morality in Christian school. This research adopts a descriptive qualitative methodology, critical analysis and argumentation to explore the intersection of moral leadership, local cultural heritage and educational leadership in Christian schools in Indonesia. As a result, the morality values of Tonaas and Walian religious leaders in Minahasa demonstrate the significance of responsibility towards the Christian school environment.Contribution: The results of this study contribute to the conversation about morality among leaders in the Christian school environment. Specifically, the religious leadership of Tonaas and Walian in Minahasa provides valuable local insights that are relevant to the context of education and principals in Indonesia.